Design optimization of a coal seam annular air reverse circulation bit - Demin Chen; Baohua Qu; Wei Long; Yanyan Li (Energy Science & Engineering, 2023)
Abstract Reverse circulation (RC) drilling technology enables the rapid acquisition of coal seam samples, which is crucial in accurately measuring gas content. In addition, the design of the drill bit plays a key role in RC sampling. In this study, the turbulence model and simulation method applied during the RC drilling process is analyzed, and an annular jet flow bit is developed. An experimental laboratory setup is used to simulate the RC performance of the proposed drill bit, based on which an orthogonal design simulation of the structural parameters of the drilling bit studies was performed to investigate the effects of the RC drilling process. The experimental results show that annular jet flow moving up the central channel wall of the bit is conducive to the suction of annular airflow and results in the strong flow field created by the center channel of the bit generating negative pressure in the center channel of the bit, a comparison of the computational fluid dynamics data on negative pressure and suction rate shows that the annular jet flow RC bit is suitable for use in RC drilling.